Two new species in Carex sect. Schoenoxiphium (Cyperaceae) from southern Africa - Márquez-Corro, José Ignacio; Maguilla, Enrique; Villaverde, Tamara; Martín-Bravo, Santiago; Luceño, Modesto (Phytotaxa, 2017)
Carex sect. Schoenoxiphium (18 spp.) is a monophyletic group that has its centre of diversity in eastern south Africa. We describe two new species from the Republic of South Africa and Lesotho on the basis of morphological characters. Both new species (C. badilloi and C. parvirufa) are closely related to C. ludwigii, C. kukkoneniana and C. pseudorufa.